Polyphenol-Enriched Pectin from Pomegranate Peel: Multi-Objective Optimization of the Eco-Friendly Extraction Process - Podetti, Celina Valeria (2023)
A multi-objective optimization was performed using response surface methodology to obtain a high-value-added product, pectin enriched in polyphenols, from pomegranate peel. For this purpose, a green extraction technique that combines citric acid and ultrasound was carried out considering three variables: time, pH, and temperature. The extraction procedure was optimized using the Box–Behnken design, these being the most suitable conditions, with an extraction time of 34.16 min, a pH of 2.2, and a temperature of 89.87 °C. At this point, the pectin yield was 31.89%, with a total retained polyphenol content of 15.84 mg GAE/g pectin. In addition, the water activity, ash content, equivalent weight, methoxyl content, and degree of esterification were determined for the pectin obtained at the optimal point. This study demonstrates that polyphenol-enriched pectin can be obtained from pomegranate peel via an eco-friendly and efficient method, and that it presents similar properties to commercial pectin, preserving its quality and with potential use as an ingredient or food supplement with a high nutritional value. This work contributes to developing sustainable strategies to valorize pomegranate agro-industrial waste and produce high-value functional ingredients.